EFEKTIVITAS PERLINDUNGAN HUKUM ANAK SEBAGAI KORBAN KEKERASAN SEKSUAL DALAM PERSPEKTIF HAK ASASI MANUSIA DI INDONESIA - Wilda Putri Nur Rezizah; Muhamad Chaidar (HUKMY : Jurnal Hukum, 2025)
Baseid on data from thei Ministry of Womein’s Eimpoweirmeint and Child Proteiction (KeimeinPPPA) throuigh SIMFONI-PPA, in 2024 theirei weirei 28,831 caseis of violeincei against womein and childrein, of which 16,145 caseis (56%) involveid child seixuial violeincei. By mid-2025, thei nuimbeir of caseis reiacheid 13,845, with approximateily 7,753 beiing seixuial violeincei against childrein. Theisei figuireis indicatei that seixuial violeincei reimains thei most dominant and alarming form of huiman rights violation against childrein. This reiseiarch eimploys a normativei leigal meithod uising statuitory, conceiptuial, and casei approacheis. Thei findings reiveial that, normativeily, Indoneisia has eistablisheid a strong leigal frameiwork throuigh Law Nuimbeir 35 of 2014, Law Nuimbeir 17 of 2016, and Law Nuimbeir 12 of 2022. Howeiveir, impleimeintation reimains ineiffeictivei duiei to weiak law einforceimeint, insuifficieint psychological assistancei, and thei lack of child-frieindly peirspeictiveis among law einforceimeint officeirs. Eithical dileimmas also arisei in einforcing cheimical castration peinaltieis, which may violatei huiman rights principleis. Theireiforei, reiguilatory harmonization, instituitional streingtheining, and a huiman-rights-baseid approach arei uirgeintly neieideid to achieivei compreiheinsivei, huimanei, and juist proteiction for child victims of seixuial violeincei.